2023
DOI: 10.51812/of.115528
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the onset of natal dispersal for a large diurnal raptor: A methodological comparison

Abstract: We estimated the onset of natal dispersal for a large diurnal raptor with high propensity towards large-scaled exploratory movements during the post-fledging period, the White-tailed Sea Eagle (Haliaeetus albicilla). We analysed GPS tracking data of 21 juveniles with respect to the onset of natal dispersal comparing six methods available from the recent literature. While none of the methods significantly differed from the visual method, the Distance Threshold method underestimated the dispersal onset for some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…All spatial calculations and visualizations were done in the ETRS89-extended/LAEA Europe Projection (EPSG-Code 3035 [33]). Dispersal [14] commenced when the young eagle left the nest site and remained >5 km away for ≥10 days [34]. End of dispersal-achieved by only one bird in the study-was identified manually by expert opinion that considered movement patterns and displacement [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All spatial calculations and visualizations were done in the ETRS89-extended/LAEA Europe Projection (EPSG-Code 3035 [33]). Dispersal [14] commenced when the young eagle left the nest site and remained >5 km away for ≥10 days [34]. End of dispersal-achieved by only one bird in the study-was identified manually by expert opinion that considered movement patterns and displacement [12].…”
Section: Discussionmentioning
confidence: 99%
“…While nesting pairs are known to be sedentary, juvenile, immature, and non-breeding, floating adults [11] move over large parts of central and eastern Europe in the course of their natal dispersion [12], which typically lasts several years in this delayedmaturity species [13]. Several studies have examined the process of natal dispersal in whitetailed eagles, and have recorded details such as timing [14], distances travelled [15,16], habitat use [17], degree of fidelity to the natal area upon recruitment [18], and the potential of human-wildlife conflicts associated with wind energy [19]. White-tailed eagles begin their dispersal from July to October of their hatch year [12] and breed in their fourth calendar year at the earliest [20].…”
Section: Introductionmentioning
confidence: 99%